Urgensi Tasawuf dalam Kajian Pendidikan Islam - Muttaqin, Muhammad (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2022)
Islamic education has so far emphasized the exoteric aspects of the esoteric aspects. This can be seen, for example, in the teaching of worship in madrasas. In teaching worship, such as prayer, more emphasis is placed on knowledge of the terms, pillars and things that invalidate them. All of this is included in the exoteric aspect. While the esoteric aspect of prayer, namely the meaning of prayer, is less emphasized. In fact, teaching the meaning of prayer is very important to form a good Muslim personality. The weak teaching of the esoteric aspects of Islam so far also means that the teaching of Sufism in Islamic education is still lacking. Whereas the teaching of Sufism should be carried out in balance with the exoteric aspects of Islam. Because without the teaching of Sufism that is balanced with exoteric aspects, the students will not appreciate the meaning of Islamic teachings. There are three problems raised in this study, namely the values ​​of Sufism teachings that are related to Islamic education, How is the series of mental education contained in the teachings of Sufism, morality and practice, What is the role of Sufism in Islamic education. The purpose of this research is to find out the values ​​of Sufism teachings related to Islamic education, to find out the series of mental education contained in Sufism teachings, especially in morality and practice Sufism, and to know the role of Sufism in Islamic education. The methodology used in this research is library research, namely library research. The primary data sources used were the book Asmaran As, Introduction to Sufism, Barmawie Umarie, Sufism System, Solihin and Rosyid Anwar, Human Sufism, Ethics, and the Meaning of Life, Sudirman Tebba, Positive Sufism, Mustafa Zahri, Keys to Understanding Sufism, Mulyadhi Kartanegara , Dive into Lubuk Sufism, Ahmad Tafsir, Education in Islamic Perspective, Ali Khalil Al-Aynayni, Philosophy al-Tarbiyyah al-Islamiyah fi Al-Qur'an al-Karim, Muhaimin, Islamic Education Thought, Mustafa Rahman, Islamic Education in Perspective Al-Qur'an and others. The secondary data sources are literature related to this research. The data collection technique uses a documentation study method, namely by collecting data sources, then reading, recording, and classifying them according to their type, then analyzing and interpreting them. The findings in this study broadly explain that: the values ​​of Sufism related to Islamic education include several aspects, namely: optimism (Raja'), consistency (Istiqamah), self-restraint (Patience), purely for the sake of Allah (Ikhlas) , do not want something worldly (Zuhud), abstain from sin (Wara'), be grateful (Syukur), righteous (Shidiq), shame (haya'), isolate oneself (Uzlah), and death (Maut) . The series of mental education contained in the teachings of Sufism, especially in moral and practical Sufism, is actually the main content and system of the teachings of Sufism itself. As in Ahlaki Sufism where mental development through the approach used is a moral approach whose stages consist of takhalli (emptying oneself of bad morals), tahalli (decorating it with commendable morals), and tajalli (opening of the barrier wall (hijab) that limits humans with Allah, so that the Divine Light is clearly visible to him, while in amali Sufism the approach used is the amaliyah approach, both physically and mentally, which then takes the form of tariqat, and takes stages in Sufism, such as: the state of repentance, the state of zuhud, the stage of tawakal and maqam ridha. The teachings of Sufism have a very important role and have very implications for Islamic education. Sufism can be said as a series or means in achieving the goals of Islamic education in fostering mental, moral and human personality so that they become human beings with noble character and gain the pleasure of Allah SWT.